2002
DOI: 10.1042/ba20010103
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the appearance of an anti‐bacterial peptide in the course of bovine haemoglobin peptic hydrolysis

Abstract: The kinetics of the alpha (1-23) peptide, which is the first anti-bacterial peptide to be isolated from a haemoglobin hydrolysate, was studied in the course of peptic hydrolysis at pH 4.5 and 23 degrees C in an homogeneous-phase system. A one-step reversed-phase HPLC coupled with photodiode array detector method was applied to identify and isolate this anti-bacterial peptide. The kinetics of peptide appearance were investigated in acetate buffer alone and in urea as a haemoglobin-denaturing agent. Two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 28 publications
0
39
0
1
Order By: Relevance
“…Choisnard et al [28] reported that during pepsin hydrolysis of protein, one molecule of pepsin cleaved the protein substrate once and then dissociated from it following one-by-one mechanism. In another case, they found one pepsin molecule would cleave the protein substrate multiple times without dissociating from it, thereby generating intermediate peptide products following a zipper mechanism.…”
Section: Hydrolysis Timementioning
confidence: 99%
“…Choisnard et al [28] reported that during pepsin hydrolysis of protein, one molecule of pepsin cleaved the protein substrate once and then dissociated from it following one-by-one mechanism. In another case, they found one pepsin molecule would cleave the protein substrate multiple times without dissociating from it, thereby generating intermediate peptide products following a zipper mechanism.…”
Section: Hydrolysis Timementioning
confidence: 99%
“…These ratios were chosen taking into account that in the previous study of hydrolysis of pure synthetic a 1-32 peptide, the ratios were 1/50, 1/100 and 1/200 [17], and that in hemoglobin, there was about ten times more peptide bonds to be hydrolyzed by pepsin than in the pure synthetic a 1-32 peptide [11,14,18].…”
Section: Hydrolysis Proceduresmentioning
confidence: 99%
“…Several studies have investigated the hydrolysis of bovine hemoglobin [11,12,[14][15][16] and numerous antibacterial peptides derived from the hydrolysis of a and b chains of hemoglobin have been identified. These active peptides are classified into four groups: two for a chain and two for b chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STC-1 pluri-endocrine cell line was derived from an endocrine tumor developed in the small intestine of double transgenic mice expressing rat insulin promoter for the simian virus 40 large T antigen and the polyoma virus small T antigen [20]. STC-1 cell line is well known for the secretion of CCK phenomenon in intestine.…”
Section: Determination Of the Degree Of Hydrolysis Of Alpha-lactalbuminmentioning
confidence: 99%